Factors influencing employee job satisfaction and turnover intention in companies in China - Zheng, Shiqian (2022)
In China, the actual employee turnover rate is relatively high and the employee's job satisfaction is at a medium level, so the research on employee job satisfaction and turnover intention is still very important. This dissertation investigates employees who have had work experience in China, using quantitative research methods, mainly researches the relationship between six influencing factors (income, employment status, corporate culture, colleague relationships, leader-employee relationship, job content) and employees' job satisfaction and turnover intention, and examines the mediating role of job satisfaction. The researcher analyzed the collected data through SPSS software and concluded that job satisfaction can significantly negatively affect turnover intention. Among the six influencing factors, corporate culture has the most significant impact on job satisfaction. In addition, job satisfaction played a mediating role in all six influencing factors explored and turnover intention, and was analyzed in comparison with previous literature. Finally, the implications and limitations of this dissertation are discussed, and the researcher provides relevant suggestions for stakeholders, which can reduce employees' turnover intention by improving their job satisfaction.